Maslow Theory Revisited-Covid-19 - Lockdown Impact on Consumer Behaviour (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current study is attempting to derive the reference to the hierarchy of Maslow, where the consumers were placed before the arrival of Covid-19 and during the lockdown time. Consumer behavior consists of cognitive, emotional or physical activities in which people pick, purchase, consume and dispose of products and services to satisfy their choices and expectations. Abraham Maslow defined hierarchy of needs in different forms viz Physiological, Safety,Social,Esteem and Self-actualization needs. A multiplicity of competing factors influences human behaviour and thereby needs and requirements.Recognition of needs is essential as the initial step for market participants in the supply chain. At the same time recognising where the needs of consumers will alter is parallelly significant for smooth functioning of market processes and securing profitability along with capturing the trend. In the present study with the help of primary survey need recognition or any sort of variation therein, pre and during the Covid-19 lockdown periodare traced within the conceptual framework of Maslow Hierarchy of needs theory.